Attention as the basic component of cognitive functions of the brain and its features in children with bronchial asthma - Nedelska, S. M.; Akulova, О. Yu.; Shumna, T. Ye.; Недельська, Світлана Миколаївна; Акулова, Олена Юріївна; Шумна, Таміла Євгенівна; Недельская, C. Н.; Акулова, Е. Ю.; Шумная, Т. Е. (Запорізький державний медичний університет, 2020)
Purpose. To study the characteristics of attention in children with bronchial asthma (BA) taking into account their sex differences, depending on the course, duration and control of the disease. Materials and methods. A psychological test (the Bourdon correction test) was performed in 101 children (71 boys and 30 girls) with BA and 30 practically healthy children (17 boys and 13 girls) aged 10–17 years who represented a control group. The test results were evaluated by the indicator S (sustained attention), calculated by the formula 0,5 × N – 2,8 × n/t, where N – the total number of characters viewed by the child in 150 seconds; n – the number of errors; t – reaction time (150 seconds). The results obtained were processed using the software package Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Results. It has been determined that BA patients demonstrated a significantly higher number of errors than healthy children: 10.1 ± 0.7 versus 7.6 ± 1.0, indicating a decrease in the sustained attention. It has been established that the uncontrolled course of the disease negatively affected the level of S that was lower than in healthy children (1.17 ± 0.05 vs. 1.32 ± 0.06) due to a decrease in attentional performance (404 ± 17 against 439 ± 19). Exacerbation and BA duration of more than 5 years led to a decrease in the level of S compared with the control group (1.24 ± 0.07 vs. 1.32 ± 0.06, P < 0.05). Depending on sex, the S score was lower in boys with BA than that in girls with BA and amounted to 1.23 ± 0.03 vs 1.39 ± 0.04 (P < 0.05) due to low attention span. However, in girls with a controlled course of BA, the S indicator even exceeded the similar indicator of healthy girls (1.52 ± 0.07 and 1.37 ± 0.09). Conclusions. Bronchial asthma children, especially boys with uncontrolled course, exacerbation and disease duration of more than 5 years, displayed attention problems as a reduction in attention span and sustained attention that should be considered as moderate manifestations of cognitive impairments. Therefore, self-management education in bronchial asthma children needs to take into account the reduced attentional indicators, and medical correction of an underlying disease should be accompanied by social and psychological support for patients. Мета роботи – вивчити особливості уваги в дітей із бронхіальною астмою (БА), враховуючи відмінності за статтю, залежно від перебігу, тривалості та контрольованості хвороби. Матеріали та методи. Використовуючи коректурну пробу Бурдона, здійснили психологічне тестування 101 дитини (71 хлопчик і 30 дівчат), які хворі на бронхіальну астму, та 30 практично здорових дітей (17 хлопчиків та 13 дівчаток) із контрольної групи віком 10–17 років. Результати проби оцінювали за показником S (стійкість уваги), який обраховували за формулою 0,5 × N – 2,8 × n/t, де N – кількість знаків, які дитина переглянула; n – кількість помилок; t – час виконання завдання (150 секунд). Результати опрацювали за допомогою пакета прикладних статистичних програм Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результати. Визначили, що кількість помилок у хворих на БА дітей вірогідно більша, ніж у здорових (10,1 ± 0,7 проти 7,6 ± 1,0), що свідчило про зниження концентрації уваги. Неконтрольований перебіг захворювання негативно впливав на показник рівня стійкості уваги (S), який був меншим, ніж у здорових (1,17 ± 0,05 проти 1,32 ± 0,06) внаслідок зниження продуктивності уваги (404 ± 17 проти 439 ± 19). Загострення і тривалість БА понад 5 років призводили до зниження показника стійкості уваги порівняно з групою контролю (1,24 ± 0,07 проти 1,32 ± 0,06, р < 0,05). У хлопчиків із БА показник S був нижчим, ніж у дівчат із БА і становив 1,23 ± 0,03 проти 1,39 ± 0,04 (р < 0,05) внаслідок низької продуктивності уваги. У дівчат із контрольованим перебігом БА показник стійкості уваги навіть перевищував від¬повідний показник здорових дівчат (1,52 ± 0,07 та 1,37 ± 0,09). Висновки. У дітей, які хворі на БА (особливо хлопчиків) із неконтрольованим перебігом, загостренням і тривалістю хвороби понад 5 років, спостерігали розлади уваги, як-от зменшення обсягу та зниження стійкості уваги, котрі потрібно розглядати як помірні прояви когнітивних розладів. Навчання дітей прийомам самоконтролю БА необхідно здійснювати, враховуючи знижені показники уваги, а медична корекція основного захворювання має супроводжуватися соціально-психологічною підтримкою хворих. Цель работы – изучить особенности внимания у детей с бронхиальной астмой (БА), учитывая отличия по полу, в зависимости от течения, длительности и контролированности заболевания. Материалы и методы. С использованием корректурной пробы Бурдона проведено психологическое тестирование 101 ребенка (71 мальчиков и 30 девочек) с бронхиальной астмой и 30 практически здоровых детей (17 мальчиков и 13 девочек) из контрольной группы в возрасте 10–17 лет. Результаты пробы оценивали по показателю S (стойкость внимания), который высчитывали по формуле 0,5 × N – 2,8 × n/t, где N – количество знаков, просмотренных ребенком; n – количество сделанных ошибок; t – время выполнения задания (150 секунд). Полученные данные обработаны при помощи пакета прикладных статистических программ Statistica for Windows 13 (StatSoft Inc., № JPZ804I382130ARCN10-J). Результаты. Установлено, что количество сделанных ошибок у детей с БА достоверно выше, чем у здоровых (10,1 ± 0,7 против 7,6 ± 1,0), что свидетельствовало о снижении концентрации внимания. Неконтролированное течение заболевания негативно влияло на показатель уровня стойкости внимания (S), который был меньше, чем у здоровых (1,17 ± 0,05 против 1,32 ± 0,06) за счет снижения продуктивности внимания (404 ± 17 против 439 ± 19). Обострение и длительность БА более 5 лет приводили к снижению показателя уровня стойкости внимания в сравнении с группой контроля (1,24 ± 0,07 против 1,32 ± 0,06, р < 0,05). У мальчиков с БА показатель S был более низким, чем у девочек с БА и составил 1,23 ± 0,03 против 1,39 ± 0,04 (р < 0,05) за счет низкой продуктивности внимания. У девочек при контролированном течении БА показатели стойкости внимания были выше соответствующего показателя здоровых девочек (1,52 ± 0,07 и 1,37 ± 0,09). Выводы. У детей с БА (особенно мальчиков) с неконтролированным течением, обострением и длительностью болезни более 5 лет, отмечены нарушения внимания в виде уменьшения объема и снижения стойкости внимания, что необходимо рассматривать как умеренные проявления когнитивных расстройств. Обучение детей приемам самоконтроля БА необходимо осуществлять, учитывая сниженные показатели внимания, а медицинская коррекция основного заболевания должна сопровождаться социально-психологической поддержкой больных.
Увага як базова складова когнітивних функцій мозку та її особливості в дітей із бронхіальною астмою
Внимание как базовая составляющая когнитивных функций мозга и его особенности у детей с бронхиальной астмой
Keywords: attention; cognitive functions; cognitive impairment; bronchial asthma; Bourdon test; children; увага; когнітивні функції; когнітивні порушення; бронхіальна астма; діти; проба Бурдона; внимание; когнитивные функции; когнитивные нарушения; бронхиальная астма; дети